2021
DOI: 10.1177/00033197211038334
|View full text |Cite
|
Sign up to set email alerts
|

Pancretic Fat Accummulation is Associated with Subclinical Atherosclerosis

Abstract: We investigated the relationship between pancreatic fat accumulation and markers of atherosclerosis among patients with nonalcoholic fatty liver disease (NAFLD). Patients with NAFLD have been reported to be at an increased risk of vascular events. We grouped 183 patients in whom we detected and graded hepatosteatosis (HS) on transabdominal ultrasonography into 2 groups based on the presence/absence of pancreatic fat. There were 85 participants (50 female; mean age: 53.6 ± 9.7 years) who were nonalcoholic fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…Age, sex, ethnicity, unhealthy lifestyle, and metabolic disorders have been recognized as the common risk factors for fatty pancreas [3,7,9]. Growing evidence has shown associations between fat content in the pancreas and the liver, suggesting a potential relationship between fatty pancreas and NAFLD [10–34]. Some research has discovered evidence that fatty pancreas contributes to fat accumulation in the liver, potentially accelerating the progression of NAFLD [18].…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, ethnicity, unhealthy lifestyle, and metabolic disorders have been recognized as the common risk factors for fatty pancreas [3,7,9]. Growing evidence has shown associations between fat content in the pancreas and the liver, suggesting a potential relationship between fatty pancreas and NAFLD [10–34]. Some research has discovered evidence that fatty pancreas contributes to fat accumulation in the liver, potentially accelerating the progression of NAFLD [18].…”
Section: Introductionmentioning
confidence: 99%
“…17 Another study also reported that NAFPD was associated with significantly increased cIMT in patients with NAFLD. 16 The study of Sahin and Karadeniz 1 increases the evidence that points to an association between abnormal fat accumulation in the pancreas and markers of atherosclerosis. Nevertheless, this association requires further evaluation.…”
mentioning
confidence: 95%
“…Age, hypertension and the presence of NAFPD were independent predictors of increased cIMT in multivariate analyses. Thus, the study of Sahin and Karadeniz 1 suggests that the presence of increased fat in the pancreas may be associated with the development of atherosclerosis in patients who also have HS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 There is also a growing body of evidence linking fatty change of the pancreas with a broad spectrum of microvascular and macrovascular changes. 3,[8][9][10] Fatty change of the pancreas was significantly associated with a higher prevalence of retinopathy in individuals with T2DM, a relationship that was the strongest in the non-obese subgroup. 8 Regarding macrovascular pathologies, fatty change of the pancreas was significantly positively associated with the thickening of carotid intima-media and a higher incidence of carotid artery plaque and vascular stiffness in individuals with and without T2DM.…”
mentioning
confidence: 98%